Long-term clinical outcomes in survivors of severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome coronavirus (MERS) outbreaks after hospitalisation or ICU admission: A systematic review and meta-analysis - Hassaan Ahmed; Kajal Patel; Darren C. Greenwood; Stephen Halpin; Penny Lewthwaite; Abayomi Salawu; Lorna Eyre; Andrew Breen; Rory O'Connor; Anthony Jones; Manoj Sivan (Medical Journals Sweden, 2020)
Objective: To determine long-term clinical outcomes in survivors of severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) coronavirus infections after hospitalization or intensive care unit admission. Data sources: Ovid MEDLINE, EMBASE, CINAHL Plus, and PsycINFO were searched. Study selection: Original studies reporting clinical outcomes of adult SARS and MERS survivors 3 months after admission or 2 months after discharge were included. Data extraction: Studies were graded using the Oxford Centre for Evidence-Based Medicine 2009 Level of Evidence Tool. Meta-analysis was used to derive pooled estimates for prevalence/severity of outcomes up to 6 months after hospital discharge, and beyond 6 months after discharge. Data synthesis: Of 1,169 identified studies, 28 were included in the analysis. Pooled analysis revealed that common complications up to 6 months after discharge were: impaired diffusing capacity for carbon monoxide (prevalence 27%, 95% confidence interval (CI) 15-45%); and reduced exercise capacity (mean 6-min walking distance 461 m, CI 450-473 m). The prevalences of post-traumatic stress disorder (39%, 95% CI 31-47%), depression (33%, 95% CI 20-50%) and anxiety (30%, 95% CI 10-61) beyond 6 months after discharge were considerable. Low scores on Short-Form 36 were identified beyond 6 months after discharge. Conclusion: Lung function abnormalities, psychological impairment and reduced exercise capacity were common in SARS and MERS survivors. Clinicians should anticipate and investigate similar long-term outcomes in COVID-19 survivors.